The Improvement of Students’ Digital Literacy Based on Environment and Local Wisdom at Public Elementary School of Oelnitep, Kefamenanu City District North Central Timor Regency: Integrating with Technology to Care for the Earth - Patricia Gertrudis Manek; Anastasia Kadek Dety Lestari; Lidwina Felisima Tae; Agustina Viktoria Tae (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
This community service was carried out to increase students’ digital literacy based on environment and local wisdom at public elementary school of Oelnitep. The activities were divided into 5 stages with the aim to produce output that is useful for partners and also for the community service team. The first stage was the initial survey in order to discuss with the school principal regarding the condition and circumstances of the school and the problems faced. The service team and the school also exchanged ideas regarding solutions to the problems of the partner. The second stage was the preparation of community service activities such as the learning media as well as the tools and materials needed. The third stage was the core activities where the students were introduced the video of “Cyber Eco Adventure: Exploring the Environment with Technology”, the Use of Google Earth, the Demo of automatic watering tools, and the practice of planting the tree saplings and making drip irrigation. Based on the results of this community service activity, it can be concluded that the use of environmental-based technology can be a way to improve digital literacy while providing basic understanding regarding the environment at public elementary school of Oelnitep.